Academic achievement, school absence and self-concept in Czech prepubescent children with overweight and obesity - Včelařová, Hana; Cakirpaloglu, Panajotis; Dostál, Daniel; Hladík, Jakub (Psychologie a její kontexty, 2022)
Problem. The paper offers findings about selected educational aspects of chil dren’s academic performance, examined here in terms of sociodemographic variables, BMI percentile values, cognitive test scores, weight bias internalization scale and self concept scale with an aim to detect whether and to what extent these factors contribute to children’s school results. Methods. 557 fifth graders were administered Vana’s Intelligence Test, the Piers ‐Harris 2 self concept questionnaire and other tools. Children’s educational aspects were assessed in terms of school Absence, Grade Point Average, and Czech and Mathematics grades, with data obtained from their most recent report cards under the Informed consent of their legal representatives and in compliance with ethical standards. Results. Prepubescent children from stronger socioeconomic backgrounds suffer from overweight/obesity less often and perform slightly better at school. The present results suggest a link between weight bias internalization and overweight/obesity, and a somewhat weaker link between selfconcept and overweight/obesity in the non clinical population of prepubescent children. In these relationships of overweight/obese children, as in the cases of alarmingly high school absence, gender is an important variable. Mul tinomial logistic regression modelling the relationship between Czech and Mathematics grades and selected factors discovered that chances for a worse grade were significantly reduced by the results of Vana’s Intelligence Test in both the subjects, while the Self ‐concept total score proved to be an insignificant factor. Conversely, pupils’ Czech grades were neg atively influenced by increased BMI (quartile), higher Absence rate, male Gender, Presence of only one parent in the family and WBI, while in Mathematics, in addition to the above discussed, significant regressors only included Absence and Presence of only one parent. Discussions. The results of the Self‐concept total score, the level of which is generally lower in girls than in boys in the population of Czech prepubescent children, agree with other authors’ experience. The connection between the male sex and poorer performance in Czech can be partly explained by the fact that the development of speech, reading, writ ing and grammar is generally less complicated for school age girls than boys. We can ask why a higher BMI quartile increases the chances of a worse grade only in the case of Czech language? So far, we can only speculate about the causes. In our opinion, it is possible that the impact of parents’ education on the performance of children of this age is more pro nounced in the Czech language (compared to Mathematics). The other possibility of the impact of the BMI quartile on the Czech grade is the significant predominance of boys in the o/o group. On the other hand, it should be noted that this argument would not explain the o/o children’s poorer Grade Point Average score. However, we believe that the above reasons answer partially this question. Conclusion. The vulnerability of o/o girls is pronounced in some domains of Self‐concept and Weight bias internalization, while in boys it is reflected in the more frequent oc currence of high levels of Absenteeism, with the precise causes of this being still subject to speculation. In this regard, workers in the cooperating professions should pay continuous attention to strengthening the desirable aspects of education and healthy lifestyle among vulnerable groups of children. Educational aspects of overweight/obese children should therefore continue to receive increased attention.